2020
DOI: 10.24256/foster-jelt.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Developing Reading Worksheet for Tenth Grade Students of SMA Negeri 4 Palopo

Abstract: This research about Developing Students' Reading Worksheet of tenth grade at SMA Negeri 4 Palopo, the researcher formulated the research question as follow: what kind of Reading Worksheet are suitable for tenth students'. The objective of this research is to create and develop reading worksheets for tenth-grade students' by using the Addie design model. In this research and development from the Addie model, this consists of Analyzing, Designing, Implementation, and evaluating. There are 14 students and two exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…It can be concluded that reading comprehension makes the students easier to understand the text that they have read (Iksan & Duriani, 2015). Reading comprehension is very important in learning because it will train the students to the goal of reading (Anwar et al, 2020). According to judith, reading comprehension is the process of comprehending the meaning of connected words that is more important in reading the text .…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that reading comprehension makes the students easier to understand the text that they have read (Iksan & Duriani, 2015). Reading comprehension is very important in learning because it will train the students to the goal of reading (Anwar et al, 2020). According to judith, reading comprehension is the process of comprehending the meaning of connected words that is more important in reading the text .…”
Section: Introductionmentioning
confidence: 99%
“…The passages that are below and above students' level should be modified to adjust students' reading levels; in addition, besides the use of English textbooks, a teacher can utilize students' worksheets in giving reading materials. Moreover, result findings conducted by Anwar, Furwana, and Iksan (2020) have mentioned that the usage of students' worksheets or known as LKPD, is remarkably beneficial for both teachers and students since it can support teachers in providing reading materials also encompasses many elements of reading, activities, and exercises.…”
Section: Resultsmentioning
confidence: 99%
“…At that point, the students' concern in understanding reading text is influenced by the method of instructing reading. In addition, the main goal of the reader is to understand the content of the reading, so the reader not just reading, but the reader should know the content of the reading contained in the text (Anwar et al, 2020). Besides, understanding student reading means that in which they can understand what they read and that students usually use their basic knowledge, vocabulary, and knowledge of grammar, the experience of texts, and strategies to help them understand the text.…”
Section: Introductionmentioning
confidence: 99%